Clinical, functional, and radiological outcome in children with pleural empyema. Issue 5 (23rd January 2019) - Maffey, Alberto; Colom, Alejandro; Venialgo, Carolina; Acastello, Eduardo; Garrido, Patricia; Cozzani, Hugo; Eguiguren, Cecilia; Teper, Alejandro
Abstract: Introduction: Few studies have prospectively evaluated recovery process and long‐term consequences of pleural space infections. Objective: To evaluate clinical, pulmonary, and diaphragmatic function and radiological outcome in patients hospitalized with pleural empyema. Material and Methods: Previously healthy patients from 6 to 16 years were enrolled. Demographic, clinical, and treatment data were registered. At hospital discharge, and every 30 days or until normalization, patients underwent a clinical evaluation, diaphragmatic ultrasound, and lung function testing. Chest radiographs were performed at subsequent visits only if abnormalities persisted. Results: Thirty patients were included. Nineteen (63%) were male, with an age of (mean ± SD) 9.7 ± 3.2 years, and body mass index (mean ± SD) 18.6 ± 3. Twelve patients (40%) were treated with chest tube drainage only, 12 (40%) exclusively with surgery, and 6 (20%) completed treatment with surgery due to an ineffective chest tube drainage. At hospital discharge, 26 (87%) of patients had abnormal breath sounds at the site of infection, 28 (93%) had a spirometric restrictive pattern, 19 (63%) diaphragmatic motion impairment, and 29 (97%) presented radiological involvement of pleural space, mainly pleural thickening. All patients had recovered diaphragmatic motion and were asymptomatic at 90‐ and 120‐day follow‐up control, respectively. Then, with a great individual variability, radiological findings, and lung function returned to normal at 60 days (range 30–180) and 90 days (range 30–180) after hospital discharge, respectively. Conclusion: Patients with pleural empyema had a complete and progressive recovery, with initial clinical and diaphragmatic motion normalization followed by radiological and lung function recovery.